Vulnerability of Baitfishes of Handline and Lift Net Fishing Gear that Landed in Kendari, Bitung, Wakatobi and Larantuka Fishing Port - Yonvitner Yonvitner; Mennofatria Boer; Masykur Tamanyira; Helmy Akbar (JURNAL PERIKANAN DAN KELAUTAN, 2019)
The high intensity of catching has an impact on decreasing stock, vulnerability, which has the potential affect to stock sustainability; such vulnerabilities include the baitfishs group in tuna fisheries. Vulnerability studies of baitfishs in Bitung, Wakatobi, Kendari and Larantuka in July 2013 were carried out to find out the pressure caused. The data collected is the parameter of productivity and perception of fish. The catches besides tuna are skipjack tuna (Katsuwonus pelamis), Indian Scad (Decapterus russelli), little tuna (Euthynuss affinis), Squid (Loligo loligo.), Anchovies (Stelophorus commersonii) and Sardinella (Sardinella fimbriata). Based on MSC (Marine Steward Council) Vulnerability Criteria, vulnerability index in Bitung (skipjack = 85.6; scad = 98.9; little tuna = 96.2), Wakatobi (scad = 97.9; squid = 98.5) and Kendari (skipjack= 85.6; anchovies = 98.5) and Sardinella fimbriata is about 96 in Larantuka. The conclusion of this research are the baitfishes state as low vulnerability and low risk and potential for sustainability